The African Continental Free Trade Area (AfCFTA) : Progress, Challenges, and Potential Benefits for Morocco - Taoufik Noujoud; Ouadghiri Kaoutar; Jbali Brahim (African Scientific Journal, 2023)
The African Continental Free Trade Area (AfCFTA) is an initiative aimed at establishing a single market for goods and services across Africa. It was signed in March 2018 and became operational on January 1, 2021. The AfCFTA aims to promote intra-African trade, enhance economic diversification, facilitate industrialization and value addition, promote small and medium-sized enterprises (SMEs), encourage investment flows, and harmonize trade and economic policies. For Morocco, joining the AfCFTA presents potential benefits. The country has made the socio-economic development of Africa a priority and was among the first countries to sign the agreement. Simulations and studies suggest that Morocco’s exports, particularly in sectors such as manufacturing industries, food, and textiles, could benefit from the AfCFTA. The agreement provides opportunities for increased trade, market access, and economic integration with other African countries. It is important to note that the implementation of the AfCFTA is an ongoing process, and its full impact will be realized over time. The collaboration and efforts of member states are crucial in realizing the potential benefits of the agreement and addressing challenges along the way.